Simple methods for determination of the acoustical properties of ground surfaces - GOŁĘBIEWSKI, Roman (Archives of Acoustics, 2007)
The interactions between the sound wave and the ground surface belong to the most important phenomena determining the outdoor noise propagation. In the present study, the exact theory of noise propagation and two simple models of the ground effect are analysed. The paper presents a method of determination of the effective flow resistivity, based on the two-channel measurement of the sound level (the exact theory). For the simplified model of the ground effect, the adjustable parameters are given as a function of the effective flow resistivity. Similarly for the ground effect model given by ISO 9613, the dependence of the ground factor (as a function of the effective flow resistivity) is presented. Additionally, for a few selected types of ground surfaces, the values of the model parameters were determined.